An analysis of genetic influence on salivary parameters and caries experience–by correlation of incidence of dental caries and salivary parameters - Pai, Deepika; Taranath, Abhay; Bhat, Sham; Sargod, Sharan (International Journal of Dental Research, 2013)
Dental Caries is a multifactorial disease where in the interplay of protective and destructive factors causes caries. The twin population is an excellent sample to study the genetic influence on the host factors responsible for caries .The caries experience in twin children is considered to be similar because of similar genetic and environmental predisposition .This study was conducted to analyze the influence of genetic control on caries experience in ten pair of twin children by analyzing the salivary parameters like flow rate , pH, viscosity and buffering capacity and by correlating it to their DMFT,def scores. The results showed no significant statistical difference in the caries experience and the salivary parameters among the twin children that were evaluated .Hence the similar caries experience in twin children can be attributed to their similar genetic and environmental factors.